A governança aplicada ao Sistema de Garantia de Direitos de crianças e adolescentes: um instrumento de acesso à ordem jurídica justa - Daniele Bellettato (2019)
The System of Guarantee of Rights of Children and Adolescents has beeninstrumentalized the Doctrine of Integral Protection and the Democratic anddecentralized Attention Policy, as established by the Constitution 1988, bringing to theLaw of the Child and Adolescent innovative tools for managing rights and capable ofguaranteeing effective access to a fair legal order. The multidisciplinary and coordinatedaction, essential to the proper functioning of the DGS, has not yet been fully assimilatedby many of its agents, who still tend to reproduce obsolete procedures provided by theCodes of Minors of 1927 and 1979, while still watching the Doctrine of IrregularSituation. Such procedures are incompatible with the Democratic State of Rights andwith the guarantor system consolidated by the Statute of the Child and the Adolescent.This is not a question of legal or normative technique, since the legal system, as it nowstands, guarantees all technical and conceptual requirements of legal science to the Lawof Children and Adolescents of 1990 (ECA/90). This is a problem related to Bourdieu'sTheory of Practice and can be solved by the application of Governance principles. Theprotectionist paradigm has introduced a new model of management of policies andprograms for child and adolescent care, essentially systemic, that requires integrationamong all agents and the various sectoral policies to ensure effective comprehensiveprotection for children and adolescents. This new paradigm is not according with theoverlapping of state structures, especially the justice system, conditioned to resolvingconflicts in a compartmentalized way and through tax and adjudicated decisions. Thesolution of conflicts in this systemic model requires that the agents assimilate and putinto practice the creative potential opened by the ECA/90, always seeking theconstruction of consensus among all agents of the network. Only through themodification of the objective structures of the procedures, through the adoption of goodgovernance techniques will it be possible to achieve effective access to the just legalorder for children and adolescents, as advocated by the Doctrine of Integral Protection.